2017
DOI: 10.1016/j.otsr.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Long and short intramedullary nails for fixation of intertrochanteric femur fractures (OTA 31-A1, A2 and A3): A systematic review and meta-analysis

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 20 publications
3
18
0
1
Order By: Relevance
“…Despite the significant differences, we were not able to correlate these results with the functional outcome. Zhang et al also demonstrated that the operative time does not influence the average length of hospital stay (25). We also found that the intraoperative blood loss was significantly higher in the long nail group.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Despite the significant differences, we were not able to correlate these results with the functional outcome. Zhang et al also demonstrated that the operative time does not influence the average length of hospital stay (25). We also found that the intraoperative blood loss was significantly higher in the long nail group.…”
Section: Discussionsupporting
confidence: 74%
“…After 12 months, the short nail group still showed better results, but not statistically significant; thus, the length of the nail may not influence the long-term functional result (P=0.28). In the literature, we found studies that demonstrated acceptable and comparable results regarding HHS (22)(23)(24)(25). Sellan et al observed a better HHS for the short nail group, but did not find any significance from the clinical point of view.…”
Section: Discussionmentioning
confidence: 74%
“…[6][7][8][9]18,19 In previous studies the comparison between short and long cephalomedullary nails focused on blood loss perioperative, time in theatre and cut out, but early and later studies do also compare complications for short and long cephalomedullary nails. A systematic review from 2017 20 comparing short and long intramedullary nails for OTA A1, A2 and A3 trochanteric fractures included 10 studies and their meta-analysis showed no difference in risk of complications, but supports the findings with reduced blood loss and time in theatre. In our study all patients were operated with third generation Gamma Nail.…”
Section: Discussionmentioning
confidence: 70%
“…. Registry studies were unable to find any differences in all-cause revision or periprosthetic fractures when comparing short to long cephalomedullary nails; long nails, however, took longer to implant and led to more estimated blood loss and hospitalization time; length of stay and mortality were similar [207][208][209][210]. A systematic review comparing short and long nails for extracapsular hip fractures was unable to demonstrate a clinically significant difference in outcome, and there is no good evidence to support long over short intramedullary devices, according to the authors [211].…”
Section: Extracapsular Hip Fracturesmentioning
confidence: 99%